Varicella zoster virus glycoprotein E-specific CD4+ T cells show evidence of recent activation and effector differentiation, consistent with frequent exposure to replicative cycle antigens in healthy immune donors. - Malavige, G; Jones, L; Black, A; Ogg, G (2008)
Varicella zoster viru (VZV)-specific T cell responses are believed to be vital in recovery from primary VZV infection and also in the prevention of viral reactivation. While glycoprotein E (gE) is the most abundant and one of the most immunogenic proteins of the virus, there are no data addressing potential T cell epitopes within gE, nor the phenotype of specific T cells. Using interferon gamma enzyme-linked immunospot assays and intracellular cytokine assays, we identified gE-specific immune responses in 20 adult healthy immune donors which were found to be dominated by the CD4+ subset of T cells. We characterized three immune dominant epitopes within gE restricted through DRB1*1501, DRB1*07 and DRB4*01, and used DRB1*1501 class II tetrameric complexes to determine the ex vivo frequency and phenotype of specific T cells. In healthy immune donors, the cells were largely positive for CCR7, CD28 and CD27, but expressed variable CD62L and low levels of cutaneous lymphocyte associated antigen with evidence of recent activation. In summary, we show that circulating gE-specific CD4+ T cells are detected at a relatively high frequency in healthy immune donors and show evidence of recent activation and mixed central and effector memory phenotype. These data would be compatible with frequent exposure to replicative cycle antigens in healthy donors and are consistent with a role for gE-specific CD4+ T cells in the control of viral replication.